Fuck yo feelings [compact disc] - Glasper, Robert (Loma Vista, 2020)
Robert Glasper releases his first set of original music under his own name since his 2016 album ArtScience. Along with being a part of several supergroups, he has played a role in some of the most important releases of this century.